Design, synthesis and biological evaluation of new phthalimide and saccharin derivatives with alicyclic amines targeting cholinesterases, beta-secretase and amyloid beta aggregation - Panek, Dawid; Więckowska, Anna; Wichur, Tomasz; Bajda, Marek; Godyń, Justyna; Jończyk, Jakub; Mika, Kamil; Janockova, Jana; Soukup, Ondrej; Knez, Damijan; Korabecny, Jan; Gobec, Stanislav; et al. (European journal of medicinal chemistry, 2017)
The complexity of Alzheimer's disease (AD) calls for search of multifunctional compounds as potential candidates for effective therapy. A series of phthalimide and saccharin derivatives linked by different alicyclic fragments (piperazine, hexahydropyrimidine, 3-aminopyrrolidine or 3-aminopiperidine) with phenylalkyl moieties attached have been designed, synthesized, and evaluated as multifunctional anti-AD agents with cholinesterase, β-secretase and β-amyloid inhibitory activities. In vitro studies showed that the majority of saccharin derivatives with piperazine moiety and one phthalimide derivative with 3-aminopiperidine fragment exhibited inhibitory potency toward acetylcholinesterase (AChE) with EeAChE IC50 values ranging from 0.83 μM to 19.18 μM. The target compounds displayed inhibition of human β-secretase-1 (hBACE1) ranging from 26.71% to 61.42% at 50 μM concentration. Among these compounds, two multifunctional agents (26, [2-(2-(4-benzylpiperazin-1-yl)ethyl)benzo[d]isothiazol-3(2H)-one 1,1-dioxide] and 52, 2-(2-(3-(3,5-difluorobenzylamino)piperidin-1-yl)ethyl)isoindoline-1,3-dione) have been identified. Compound 26 exhibited the highest inhibitory potency against EeAChE (IC50 = 0.83 μM) and inhibitory activity against hBACE1 (33.61% at 50 μM). Compound 52 is a selective AChE inhibitor (IC50 AChE = 6.47 μM) with BACE1 inhibitory activity (26.3% at 50 μM) and it displays the most significant Aβ anti-aggregating properties among all the obtained compounds (39% at 10 μM). Kinetic and molecular modeling studies indicate that 26 may act as non-competitive AChE inhibitor able to interact with both catalytic and peripheral active site of the enzyme.
Keywords: molekulární struktura; lékové transportní systémy; Amines; cholinesterasy; Humans; vazebná místa; Amyloid Precursor Protein Secretases; Enzyme Inhibitors; ftalimidy; lidé; Drug Delivery Systems; sacharin; inhibitory enzymů; Protein Aggregation, Pathological; racionální návrh léčiv; aminy; Protein Binding; Binding Sites; hematoencefalická bariéra; sekretasy; amyloidní beta-protein; Saccharin; peptidové fragmenty; Molecular Structure; inhibiční koncentrace 50; Cholinesterases; Inhibitory Concentration 50; patologická konformace proteinů; Drug Design; vazba proteinů; Amyloid beta-Peptides; Phthalimides; Peptide Fragments; Blood-Brain Barrier